AWAS: Auto Weigh Air Sorter Untuk Memilah Barang Berdasarkan Berat Di Bandara - Fauzan Adityo; Wafiq Nurhanafi; Rahmat Hidayat (Jurnal Komputer dan Elektro Sains, 2024)
Auto Weigh Air Sorter (AWAS) is a technological innovation designed to sort items based on weight at airports. This system uses Arduino as a controller and a load cell as a weight sensor. Items are sorted using a servo motor based on the data obtained from the sensor. The aim of AWAS is to improve efficiency and accuracy in baggage handling, thereby speeding up the process of pricing and baggage handling. Thus, AWAS have the potential to make a significant contribution to the aviation industry by improving service quality to passengers and reducing baggage waiting time. This research focuses on the design, implementation, and evaluation of the AWAS system, as well as its potential application in the airport context.